1993
DOI: 10.1002/pssa.2211390108
|View full text |Cite
|
Sign up to set email alerts
|

Studies on CdSxSe1−x films prepared by two-zone hot wall technique

Abstract: Polycrystalline thin films of CdSxSe1−x (0 < x < 0.8) are prepared by co‐evaporating CdS and CdSe from a two‐zone evaporation source. The films are characterised by measuring optical and electrical properties. Information on the microstructures are obtained from XRD and TEM/SEM measurements. Raman shifts in the films with composition are also reported. Information on the scattering mechanism is derived from the thermoelectric power measurements. Grain boundary scattering effects in these films are also studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The ratio of photo to dark conductivity is also an important parameter for the photosensitive films. In the earlier studies , researchers found that for polycrystalline CdS x Se 1– x films, the electrical conductivity was mainly governed by the barrier height at the grain boundary region. The barrier height could be sharply decreased with increasing intensity of the incident light, which will cause an increment in electrical conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…The ratio of photo to dark conductivity is also an important parameter for the photosensitive films. In the earlier studies , researchers found that for polycrystalline CdS x Se 1– x films, the electrical conductivity was mainly governed by the barrier height at the grain boundary region. The barrier height could be sharply decreased with increasing intensity of the incident light, which will cause an increment in electrical conductivity.…”
Section: Resultsmentioning
confidence: 99%